Profil Peternakan Babi Di Kota Kupang Dan Potensi Penularan Trichinellosis - Andrijanto Hauferson Angi; Fadjar Satrija; Denny Widaya Lukman; Mirnawati Sudarwanto; Etih Sudarnika (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Trichinellosis is a parasitic disease of humans caused by eating raw from domestic or game animals infected by Trichinella spp. Human trichinellosis contracted from commercial supplies of meat have been most often linked to infected pigs, wild boar, or horses. Trichinella is a nematode which has an atypical direct life cycle that does not involve stages developing outside of the host. This study was conducted to see the profile of pig farms in the city of Kupang and the potential transmission of trichinellosis. The data was derived from interview 60 farmers in 6 sub districts in city of Kupang by using a structured questionnaire and analyzed descriptively. The results of the questionnaire survey showed that many race of pig from a mixed race, the seeds come from traditional breeding. Feed rest of the home or restaurant are usually directly given to the pigs. The presence of rat in around of the cage often. All respondents were interviewed did not know or hear about trichinellosis disease which can be one cause of the spread of trichinellosis in city of Kupang.